Fernando Degiovanni, Vernacular Latinamericanisms. War, the Market, and the Making of a Discipline - Rojas, Rafael (Prismas - Revista de historia intelectual, 2020)
Fernando Degiovanni, Vernacular Latinamericanisms. War, the Market, and the Making of a Discipline, Pittsburgh, University of Pittsburgh Press, 2018, 238 páginas